Effect of Temperature on the Minimum Cathodic Protection Potential of L450 Pipeline Steel - CHEN Meng-meng, TAO Wen-jin, MA Yu, LIAO Zhen, MA Xiao-feng, LV Xiang-hong, WANG Chen (Cailiao Baohu)
Aiming at the effect of temperature on the minimum cathodic protection potential, the minimum cathodic protection potential of the buried pipeline L450 in the simulated soil solution under different temperature conditions was investigated through the tests of potentiodynamic polarization and potentiostatic polarization, and the technical means such as weight loss method and anodic Tafel straight-line segment back-propagation method for achieving the best protection state of cathodic protection system, avoiding the phenomenon of pipeline corrosion perforation caused by insufficient cathodic protection and thus improving the applicability and correctness of pipeline corrosion protection scientifically and effectively. Results showed that for pipelines with operating temperature ≤40 ℃, the minimum cathodic protection potential should be EP ≤-850 mV(vs CSE, the same below). For pipelines with operating temperature ranging from 40 ℃ to 60 ℃, the minimum cathodic protection potential should be-850 mV≤EP≤-950 mV. For pipelines with operating temperature ranging from 60 ℃ to 80 ℃, the minimum cathode protection potential should be-950 mV≤EP≤-1 000 mV. The pipelines with operating temperature ranging from >80 ℃ obtained EP≤-1 000 mV.